Sosialisasi Dan Pelatihan Penyusunan Pembukuan Sederhana Menggunakan Aplikasi Bukuwarung Pada UMKM Menengah : (Studi Kasus Pada Pelaku UMKM Pasar Bringharjo) - Rizki Nur Khasanah; Diana Airawaty (Sejahtera: Jurnal Inspirasi Mengabdi Untuk Negeri, 2024)
This Community Service activity aims to provide training in preparing simple bookkeeping for Mengehah Micro Small Enterprises (MSMEs) at Bringharjo Market. This service partner involves 5 MSME players who have businesses on the left side of the Beingharjo market. The activities will be carried out on 18 September, 7, 15 October and 28 October 2023. Activities are carried out by visiting MSME partners one by one. The results of this service show that there are still many MSME players who do not know how to prepare simple bookkeeping. Therefore, the service provides assistance in preparing simple bookkeeping to make it easier to record financial reports and for the sustainability of the business of MSMEs at Bringharjo Market.